2023
DOI: 10.1002/smtd.202201557
|View full text |Cite
|
Sign up to set email alerts
|

Understanding and Optimizing Capacitance Performance in Reduced Graphene‐Oxide Based Supercapacitors

Abstract: Reduced graphene-oxide (RGO)-based electrodes in supercapacitors deliver high energy/power capacities compared to typical nanoporous carbon materials. However, extensive critical analysis of literature reveals enormous discrepancies (up to 250 F g −1 ) in the reported capacitance (variation of 100-350 F g −1 ) of RGO materials synthesized under seemingly similar methods, inhibiting an understanding of capacitance variation. Here, the key factors that control the capacitance performance of RGO electrodes are de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 79 publications
0
5
0
Order By: Relevance
“…The XRD patterns are shown in Figure d. All rGO and FG- T samples exhibited an amorphous hump at about 24°, which was due to the fact that low-temperature calcination partially removed the oxygen-containing functional groups and reduced a small amount of the CC bonds. , In addition, the F atoms only partially replaced the oxygen-containing functional groups and could not completely cover the entire GO base surface. Therefore, surface defects cause a low crystallinity in FG- T samples.…”
Section: Resultsmentioning
confidence: 99%
“…The XRD patterns are shown in Figure d. All rGO and FG- T samples exhibited an amorphous hump at about 24°, which was due to the fact that low-temperature calcination partially removed the oxygen-containing functional groups and reduced a small amount of the CC bonds. , In addition, the F atoms only partially replaced the oxygen-containing functional groups and could not completely cover the entire GO base surface. Therefore, surface defects cause a low crystallinity in FG- T samples.…”
Section: Resultsmentioning
confidence: 99%
“…Reduced graphene oxide (rGO) with excellent mechanical flexibility and stability, high electrical conductivity, high surface area, and light weight has been regarded as an attractive substrate to fabricate multicomponent hybrid nanostructures with high capacity and good stability. The introduction of a rGO layer can improve the surface charge accumulation and electron collection efficiency of NiCo 2 O 4 species, as explained in a density functional theory (DFT) study, which is beneficial for enhancement of the redox activity of NiCo 2 O 4 .…”
Section: Introductionmentioning
confidence: 99%
“…Carbon nanomaterials (Yan et al, 2023) have attracted worldwide attention since they have demonstrated great potential in energy storage (Fu et al, 2023;Gadipelli et al, 2023;Gao et al, 2023;Mo et al, 2023;Senokos et al, 2023) and conversion (Zhang et al, 2022;Kim et al, 2023;Lv et al, 2023;Peng et al, 2023) to relieve the environmental problem and energy crisis (Gao et al, 2022;Marangon et al, 2023;Yan et al, 2023). Carbon nanomaterials also play a significant role in the field of electrocatalysis of ORR due to their low cost, high performance and excellent stability (Zaman et al, 2022a).…”
Section: Introductionmentioning
confidence: 99%